Corneal changes in progressive keratoconus after cross-linking assessed by Scheimpflug camera - Kránitz, Kinga; Knorz, Michael C. (Journal of refractive surgery, 2012)
Journal of Refractive Surgery | PURPOSE: To evaluate corneal changes after corneal cross-linking (CXL) in progressive keratoconus with Scheimpflug imaging. METHODS: This prospective analysis included 40 eyes from 22 patients with progressive keratoconus. Corneal CXL was performed in 25 eyes (CXL group) and 15 fellow eyes served as controls (control group). Uncorrected (UDVA) and corrected distance visual acuity (CDVA),